Fact vs. Speculation: Finding the Meaning Behind the Westmoreland Slaughterhouse, Pottawatomie County, Kansas, 1859 – 1959 - Zuk, Lara (Kansas State University, The Chapman Center for Rural Studies, 2010)
With Germanic and possibly surviving medieval European culture ways implanted in Pottawatomie County, a shared rural slaughterhouse in early Westmoreland provides clues. From oral accounts only, the author locates the site of the original slaughterhouse and discusses its use as a shared resource by early German farmers in the area. This study contains interviews and photographs.
Lara Zuk, “Fact vs. Speculation: Finding the Meaning Behind the Westmoreland Slaughterhouse, Pottawatomie County, Kansas, 1859 – 1959,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/216.
Keywords: Charles Sutterlin; John McKimens Sr.; Marian Bradley; Pottawatomie County; Westmoreland; Westmoreland Slaughterhosue